Tooth number abnormality: from bench to bedside - Han Zhang; Xuyan Gong; Xiaoqiao Xu; Xiaogang Wang; Yao Sun (Nature Publishing Group, 2023)
Abstract Tooth number abnormality is one of the most common dental developmental diseases, which includes both tooth agenesis and supernumerary teeth. Tooth development is regulated by numerous developmental signals, such as the well-known Wnt, BMP, FGF, Shh and Eda pathways, which mediate the ongoing complex interactions between epithelium and mesenchyme. Abnormal expression of these crutial signalling during this process may eventually lead to the development of anomalies in tooth number; however, the underlying mechanisms remain elusive. In this review, we summarized the major process of tooth development, the latest progress of mechanism studies and newly reported clinical investigations of tooth number abnormality. In addition, potential treatment approaches for tooth number abnormality based on developmental biology are also discussed. This review not only provides a reference for the diagnosis and treatment of tooth number abnormality in clinical practice but also facilitates the translation of basic research to the clinical application.